Arctic Species Trend Index: Key Findings from an In-depth Look at Marine Species and Development of Spatial Analysis Techniques - Earner, J.; Russell, D.E.; McRae, L.; Delnet, S.; Collen, B.; Gill, M.J. (Conservation of Arctic Flora and Fauna (CAFF), 2012)
"This report builds on the CAFF report The Arctic Species Trend Index 2010: Tracking trends in Arctic wildlife. This report provides an update of the overall index, an exploration of the data sets using spatial analysis techniques, and a more in-depth examination of the data sets for marine vertebrates. The report is based on two technical reports prepared for CAFF. The report contains a plain language summary of the ASTI methods, as well as a table showing the time spans and sample sizes for the various analyses described."